Plastic surgery for the treatment of contagious diseases: lobomycosis - Rodolfo Luis Korte; Cipriano Ferreira-Junior; Ana Elisa Kadri Castilho; Laryssa Fernanda Feitosa; Anita Sperandio Porto (Revista Brasileira de Cirurgia Plástica)
Introduction: Lacaziosis is a rare disease that mainly affects workers in tropical areas, with approximately 500 cases reported worldwide. Lacaziosis is a parasitic disease caused by the saprophytic fungus Lacazia loboi; there is no specific treatment for this disease. Surgery is the most effective treatment for the deformities caused by the disease. However, it is a temporary treatment, since disease recurrence is frequently observed. Lacazia loboi affects two species of dolphin, Tursiops truncates and Sotalia guianensis. The available literature discusses the surgical treatment in a superficial way , because there are no specific studies describing the surgical treatment for this disease. Methods: Here, we describe our 8 years of experience with lacaziosis at the Hospital de Base de Porto Velho - Rondônia; a total of 22 patients underwent surgical treatment and were followed-up. Results: The majority of the patients (91%) had already submitted to at least one surgical treatment together with antifungal treatment. The patients presented with lesions with disease progression ranging from 5 months to 6 years prior to surgical treatment. Only two patients were treatment-naive. Conclusion: Our patients were followed-up; however, only 11 of the 22 patients returned for follow-up. Recurrences were observed in 9 of the 11 patients, with a latency period of 5 months.